2007
DOI: 10.1080/01443610701718883
|View full text |Cite
|
Sign up to set email alerts
|

Abortion-related mortality in a tertiary medical centre in Enugu, Nigeria

Abstract: This study reviewed abortion-related maternal deaths, from January 2000 to December 2005 at the University of Nigeria Teaching Hospital, Enugu, Nigeria, to identify maternal characteristics, abortion types, provider characteristics, complications and causes of death. Abortion was defined as termination of pregnancy before 28 completed weeks of pregnancy. There were 93 pregnancy-related deaths, and 11 were abortion-related. Abortion-related mortality accounted for 11.8% of all maternal deaths. Nine (81.8%) had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…The vast majority of abortion‐related deaths occur in Sub‐Saharan Africa (about 36 000) and south Central Asia (about 28 400), whereas the number is negligible in southern and western Europe, North America and China (3). In Tanzania, a recent review of 113 maternal deaths suggested that 14 (12%) women had died following an unsafe abortion (24), while in Nigeria 12–13% of maternal deaths have been reported to be due to unsafe abortion (25,26). The reported figures from Tanzania and Nigeria are in accordance with the global estimate of unsafe abortion accounting for 13% of all maternal deaths (3).…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of abortion‐related deaths occur in Sub‐Saharan Africa (about 36 000) and south Central Asia (about 28 400), whereas the number is negligible in southern and western Europe, North America and China (3). In Tanzania, a recent review of 113 maternal deaths suggested that 14 (12%) women had died following an unsafe abortion (24), while in Nigeria 12–13% of maternal deaths have been reported to be due to unsafe abortion (25,26). The reported figures from Tanzania and Nigeria are in accordance with the global estimate of unsafe abortion accounting for 13% of all maternal deaths (3).…”
Section: Resultsmentioning
confidence: 99%
“…Across the world, students in higher institutions of learning constitute an influential group of young people. Studies from South East Nigeria have shown that the level of sexual activity among young people in tertiary educational institutions is high,2 and that complicated illegally induced abortion for unwanted pregnancy has increased five-fold over the previous decades with significant abortion-related mortality 3,4. In addition, Enugu state has one of the highest rates of human immunodeficiency virus infection among pregnant women in Nigeria 5.…”
Section: Introductionmentioning
confidence: 99%
“…
Induced abortion is legally restricted in Nigeria; it is permitted only to save the life of the woman and, in the southern states of the country, also for physical and men-tal health reasons (Ogiamien 2000). Despite the restrictive abortion law, several reports (Okonofua et al 1999;Nwogu-Ikojo and Ezegwui 2007;Bankole et al 2008) indicate that induced abortion is widespread in the country and that it is associated with high rates of maternal morbidity and mortality. Data from the Federal Ministry of Health suggest that complications of induced abortion account for an estimated 20 percent of maternal deaths in Nigeria.
…”
mentioning
confidence: 99%
“…A study of women in two states of Nigeria (Okonofua et al 1999) revealed that more than 30 percent of the women who indicated that their abortions were performed by private medical providers mentioned that they had experienced significant complications following the abortion procedure. Similarly, audits of complications and deaths associated with unsafe abortion in various parts of the country indicate that most abortion procedures that resulted in severe complications and hospitalizations were carried out by private medical providers (Nwogu-Ikojo and Ezegwui 2007). Our previous study of private medical practitioners, which drew upon 2001 data and did not include questions on medical abortion, revealed that although up to 40 percent reported that they operate a policy of terminating unwanted pregnancies in their clinics, many did not employ current evidence-based procedures for doing so .…”
mentioning
confidence: 99%